Magnifying Endoscopy with Narrow Band Imaging to Determine the Extent of Resection in Transoral Robotic Surgery of Oropharyngeal Cancer. (9th December 2014) - Tateya, Ichiro; Ishikawa, Seiji; Morita, Shuko; Ito, Hiroyuki; Sakamoto, Tatsunori; Murayama, Toshinori; Kishimoto, Yo; Hayashi, Tomomasa; Funakoshi, Makiko; Hirano, Shigeru; Kitamura, Morimasa; Morita, Mami; et al.
Abstract : Transoral robotic surgery (TORS) is a less invasive treatment that is becoming popular all over the world. One of the most important factors for achieving success in TORS is the ability to determine the extent of resection during the procedure as the extent of resection in the laryngopharynx not only affects oncological outcomes but also directly affects swallowing and voice functions. Magnifying endoscopy with narrow band imaging (ME-NBI) is an innovative optical technology that provides high-resolution images and is useful in detecting early superficial pharyngeal cancers, which are difficult to detect by standard endoscopy. A 55-year-old male with superficial oropharyngeal cancer has been successfully treated by combining MB-NBI with TORS and MB-NBI was useful in determining the extent of resection. ME-NBI with TORS will make it possible to achieve a higher ratio of minimally invasive treatment in pharyngeal cancer.